Correlation between Sonoelastographic, Doppler and Histopathological Findings in Chronic Kidney Disease Patients in Tertiary Care Centre - Jha, S. K.; Lohani, B.; Pant, A. D.; Chataut, D.; Regmi, D.; Bhatta, U.; Gautam, N.; Jha, G. (Kathmandu University Medical Journal, 2022)
Background Ultrasound (USG) with Doppler examination of intrarenal vessels is the imaging modality of choice employed in patients with renal failure and is commonly performed early in the clinical course. The pulsatility index (PI) and the resistive index (RI) of downstream renal artery have been found to correlate with renal vascular resistance, filtration fraction and effective renal plasma flow in chronic renal failure. Pathological process in any tissues alters their elastic properties which can be assessed non-invasively through newer technique like elastography.Objective To correlate the findings obtained by sonoelastographic, doppler and histopathological studies in chronic kidney disease patients.Method Study was done in 146 patients referred to Department of Radiodiagnosis and Imaging, TUTH for native renal biopsy. Renal sonographic morphology (length, echogenicity, cortical thickness), Sonoelastography (Young’s modulus) and Doppler parameters (peak systolic velocity, resistive index) were assessed. The grading of estimated GFR (eGFR) was calculated based on chronic kidney disease (CKD) criteria.Result Among 146 patients, 63 (43.2%) were females and 83 (56.8%) were males. Maximum patients were in age group of 41-50 years (25.3%) followed by age group 51-60 years (24%). Mean age of patient was 42.06±14.70 for males and 39.57±12.54 females. Maximum mean Young’s modulus was seen in eGFR stage G1 with 46.57±19.51 kPa followed by in stage G3a with 36.46±10.01 kPa and observed to be statistically non-significant (p=0.172). However, statistical significance difference was noted between the resistive index and elastographic measurement of Young’s modulus (r=0.462, p=0.0001). Minimum mean cortical thickness was seen in eGFR stage G5 with 4.42±1.48 mm followed by stage G4 with 5.57±1.24 mm (p= 0.0001). Cortical thickness is decreasing as eGFR stage was increasing in our study (p=0.0001). Resistive index is increasing with decrease in renal size (r=-0.202, p=0.015).Conclusion Ultrasonography along with doppler study and elastography have limited role in diagnosing the pathology of chronic kidney disease, however, it has significant role in the disease progression.